2013
DOI: 10.1371/journal.pgen.1003958
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Studies Implicate Synaptic Overgrowth and Ring Gland cAMP/PKA Signaling Defects in the Drosophila melanogaster Neurofibromatosis-1 Growth Deficiency

Abstract: Neurofibromatosis type 1 (NF1), a genetic disease that affects 1 in 3,000, is caused by loss of a large evolutionary conserved protein that serves as a GTPase Activating Protein (GAP) for Ras. Among Drosophila melanogaster Nf1 (dNf1) null mutant phenotypes, learning/memory deficits and reduced overall growth resemble human NF1 symptoms. These and other dNf1 defects are relatively insensitive to manipulations that reduce Ras signaling strength but are suppressed by increasing signaling through the 3′-5′ cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 101 publications
5
50
0
Order By: Relevance
“…Whether the neurofibromin PH domain associated with 5-HT 6 receptor favors recruitment of Gs protein remains to be explored. A recent study has shown that the regulation by neurofibromin of cAMP signaling requires Ras activation and operates through the activation of atypical PKC zeta (28), whereas other studies performed in Drosophila suggest that neurofibromin controls cAMP production in an Ras-independent manner (19,29). Our results showing that expression of PH domain alone is sufficient to rescue normal 5-HT 6 receptor constitutive activity in neurofibromin-deficient cells are consistent with an Ras-independent mechanism.…”
Section: Discussionsupporting
confidence: 80%
“…Whether the neurofibromin PH domain associated with 5-HT 6 receptor favors recruitment of Gs protein remains to be explored. A recent study has shown that the regulation by neurofibromin of cAMP signaling requires Ras activation and operates through the activation of atypical PKC zeta (28), whereas other studies performed in Drosophila suggest that neurofibromin controls cAMP production in an Ras-independent manner (19,29). Our results showing that expression of PH domain alone is sufficient to rescue normal 5-HT 6 receptor constitutive activity in neurofibromin-deficient cells are consistent with an Ras-independent mechanism.…”
Section: Discussionsupporting
confidence: 80%
“…Su(H)‐LacZ [ Su(H) GBE ‐LacZ , (Furriols & Bray, 2001)], esg‐Gal4 NP7397 , UAS‐GFP , tub‐Gal80 TS chromosome (gift from J. de Navascués), Ret‐Gal4 (Walker et al , 2013), wg KO ‐Gal4 (Alexandre et al , 2014; gift from Luis‐Alberto Baena‐Lopez).…”
Section: Methodsmentioning
confidence: 99%
“…Second, whereas only relatively widespread neuronal dNf1 re-expression restored the mutant growth defect, 12 in the current study, genetic manipulations that increased cAMP/PKA signaling in specific parts of the larval ring gland (a neuroendocrine gland analogous to the mammalian pituitary) were sufficient to restore dNf1 growth. By contrast, expressing dNf1 in the ring gland or widespread neuronal expression of a dnc RNAi transgene outside of the ring gland had no effect 14 . These results argue that dNf1 controls Drosophila growth by non-cell-autonomously affecting cAMP/PKA signaling in the ring gland (Fig.…”
mentioning
confidence: 85%
“…Supporting an evolutionary conserved functional link between both proteins, mutations that activate ALK or that block the expression of NF1 have both been implicated in neuroblastoma tumorigenesis 24 , 25 . Adding to this indirect evidence, our recent study found that shRNA-mediated suppression of NF1 expression renders human neuroblastoma cells resistant to pharmacological ALK inhibition 14 . Specifically, we used two human neuroblastoma lines harboring constitutively active F1174L ALK alleles.…”
mentioning
confidence: 97%
See 1 more Smart Citation